PERILAKU IBU RUMAH TANGGA DALAM PENGELOLAAN SAMPAH DI KECAMATAN PAUH KOTA PADANG - Nurfadila Rahmi; Ernawati Ernawati (Universitas Negeri Gorontalo, 2021)
The research objective aims to determine the behavior of housewives about 1) knowing where the housewives dispose of waste in Pauh Subdistrict, Padang City, 2) knowing the condition of the waste disposed of by housewives in Pauh Subdistrict, Padang City, 3) knowing whether housewives carry out waste management in Pauh District. The research method used is descriptive qualitative. The research instruments were housewives in Pauh District, Padang City, totaling 75 people. The data collection technique was done by means of observation, interview and documentation. The data analysis technique used is the analysis process of data reduction, data presentation, and data verification. The results of the research on the behavior of housewives in waste management in Pauh Subdistrict, Padang City show that, 1) the location of the housewives' garbage disposal is around the riverbank, on the side of the road, in the middle of the street park, TPS or temporary shelter, behind the house and in the yard. . 2) housewives do not do waste sorting before disposing of garbage, so that the condition of the waste to be disposed of is mixed together. 3) found in all PauhSubdistricts, only a few housewives know how to sort waste, recycle waste, and use sprouts into items of economic value. The waste management used is the Landfill management model or just letting the waste rot.